2016
DOI: 10.1055/s-0036-1586749
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ex Vivo Training Model for Acquiring Supermicrosurgical Skills Using a Chicken Leg

Abstract: Supermicrosurgery is a technique used for dissection and anastomosis of submillimeter diameter vessels. This technique requires precise hand movements and superb eye-hand coordination, making continuous training necessary. Biological in vivo and ex vivo models have been described for this purpose, the latter being more accessible and cost-effective. The aim of this study is to present a new ex vivo training model using a chicken leg. In 28 chicken legs, an anatomical study was performed. An intramuscular perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Models, such as the silicone tube model and the training card model, 15 have been suggested as instruction tools for supermicrosurgery. Cifuentes et al 16 identified 0.7 to 0.3 mm diameter arteries in chicken legs and confirmed the consistency of the perforator. While they are easy to obtain, less expensive, and involve no ethical conflicts, they have no dynamic blood circulation.…”
Section: Discussionmentioning
confidence: 74%
“…Models, such as the silicone tube model and the training card model, 15 have been suggested as instruction tools for supermicrosurgery. Cifuentes et al 16 identified 0.7 to 0.3 mm diameter arteries in chicken legs and confirmed the consistency of the perforator. While they are easy to obtain, less expensive, and involve no ethical conflicts, they have no dynamic blood circulation.…”
Section: Discussionmentioning
confidence: 74%
“…Nowadays, nonliving specimen such as chicken thigh model can simulate micro-(vessel diameter > 0.8 mm) and supramicroanastomoses (diameter 0.3-0.8 mm). 21,22 Due to the smallest needle gauge we had and size of human hair, our DIY microsuture was proper for practicing microsurgical anastomosis in vessel diameter larger than 0.8 mm.…”
Section: Discussionmentioning
confidence: 99%
“…21 A simple chicken leg model for supermicrosurgery skill development has also been described for vessels between 0.3 and 0.7 mm. 22 Two commonly described techniques for end-to-end anastomosis include the biangulation technique and the triangulation technique. The biangulation technique involves two stay sutures, each at 180 degrees; while the triangluation technique places three stay sutures, each at 120 degrees.…”
mentioning
confidence: 99%